Dynamic stability of a rotor with shear-flexible shaft under axial loads - Yim, K. B.; Yim, J. T. (Journal of mechanical science and technology, 2013)
The dynamic stability of shear-flexible rotating shaft with a disk under axial forces has been studied by employing the transfer matrix method. The conventional transfer matrix was modified to include both the applied axial force and the shear deformation. The shear effect is considered based on Engesser’s and Haringx’s buckling theories for shear-flexible beam. A computer program was developed to investigate the influence of both the axial force and the shear deformation on the stability and the natural frequencies of general rotor systems. Two rotor system models are considered: the overhung rotor with or without an intermediate support and the simply supported Jeffcott rotor. The effect of shear deformation and the difference between the Engesser and Haringx approaches increase with an intermediate support for an overhung rotor.